'This is a land of honey – no milk, bar sour!' African milk regimes and the emergence of a colonial order in Southern Rhodesia 1890s–1907. Issue 2 (3rd May 2016) - Hove, Godfrey; Swart, Sandra
Abstract : This paper focuses on African milk regimes, and their response to the emergence of a hegemonic colonial order, with its exploitative and racially prejudicial tendencies during the first few years of occupation. It explores the interface between African beliefs and systems and the predominantly market-based European dairy regime. We demonstrate that, notwithstanding the symbolic values of milk in African societies, the notion of an African milk complex is misplaced since Africans were not only receptive, but also thrived on the colonial milk market during the first three years of occupation. Further, we posit that, despite African willingness to participate in the dairy market, the extent of their prosperity thereon became markedly reduced after the 1893 War of Dispossession, due to cattle losses and bovine diseases that ravaged the colony during the early years of occupation. In the process, we engage and challenge scholarship that has portrayed the first two decades of colonial occupation in Southern Rhodesia as an era of peasant prosperity.